Preoperative nutrition and postoperative liver function: a correlation study of pediatric living donor liver transplantation - Lu Ye-Feng; Wang Yan; Huang Ming-Zhu; Ren Xue-Fei; Gao Lei-Qing; Li Dan; Li Yan-Fen; Yang Yan (Sciendo, 2018)
There is little information focusing on the nutritional issue of pediatric recipients before they receive living donor liver transplantation. This study illustrates the relationship between nutritional status and graft liver function and provides a reference regarding nutritional interventions in future studies.